The relationship between obstructive sleep apnea and circulating tau levels: A meta‐analysis - Zhi‐Wei Huang; Hui‐Xue Zeng; Ya‐Ping Huang; Tie‐Zhu Wang; Wen‐Sen Huang; Yan‐Fei Huang; Li Lin; Hao Li (Brain and Behavior, 2023)
Abstract Background Alzheimer's disease (AD) is an irreversible, progressive brain disorder that impairs memory, thinking, language, and, eventually, the ability to carry out the simplest of tasks. Tau protein, the major component of neurofibrillary tangles, is considered a key mediator of AD pathogenesis. The association between obstructive sleep apnea (OSA) and circulating tau remains unclear. The aim of the present meta‐analysis was to evaluate the relationship between OSA and circulating tau via quantitative analysis. Methods A systematic search of Pubmed, Embase, and Web of Science were performed. The mean values of circulating total tau (T‐tau) and phosphorylated tau (P‐tau) in OSA and control groups were extracted. Standardized mean difference (SMD) with 95% confidence interval (CI) was calculated by using a random‐effect model or fixed‐effect model. Results A total of seven studies comprising 233 controls and 306 OSA patients were included in this study. The meta‐analysis showed that the circulating T‐tau level was significantly higher in OSA patients than those in the control group (SMD = 1.319, 95% CI = 0.594 to 2.044, z = 3.56, p < .001). OSA patients also had significantly higher circulating P‐tau level than control group (SMD = 0.343, 95% CI = 0.122 to 0.564, z = 3.04, p = .002). Conclusions The present meta‐analysis demonstrated that both circulating T‐tau and P‐tau levels were significantly increased in OSA subjects when compared with non‐OSA subjects. Larger sample‐size studies on the association between OSA and circulating tau are still required to further validate our results.